Impact of oxygen availability on heterologous geneexpression and polypeptide secretion dynamics in Yarrowia lipolytica‐based protein production platforms. Issue 9 (26th June 2020) - Gorczyca, Maria; Kaźmierczak, Jan; Steels, Sebastien; Fickers, Patrick; Celińska, Ewelina
Abstract: Industrially relevant traits of Yarrowia lipolytica, like high growth rate, capacity to grow at high cell density or to synthesize biomolecules with high productivities, strongly rely on sufficient oxygen provision. Although the impact of oxygen availability (OA) on the physiology of Y. lipolytica has been already studied, its influence on recombinant protein (rProt) synthesis and secretion has been largely neglected to date. With the aim to fill this gap, a fluorescent reporter protein (yellow fluorescent protein [YFP]) was used herein as a proxy to follow simultaneously rProt synthesis and secretion in Y. lipolytica under different OAs. This study covers the analysis of the reporter gene expression through reverse transcription quantitative polymerase chain reaction, polypeptide synthesis and its retention‐to‐secretion ratio using flow cytometry and fluorymetry during shake flasks and bioreactor cultivations under different OA. The results gathered demonstrate that OA has a dramatic impact on the kinetics of intracellular and extracellular YFP accumulation. Higher rProt production and secretion were favoured under high OA, and were largely related to OA and not to cell growth. Our observations also suggest the existence of some upper limit of secretory protein accumulation inside the cells above which massive secretion is initiated. Moreover, at low OA, the first bottleneck in rProt synthesis occurs as early as at transcription level, which could results from a lower availability of transcriptional machinery elements. Finally, using flow cytometry and bioreactor cultivations, we highlighted that ovoid cells are generally more efficient in terms of rProt synthesis.